CES 2019
DOI: 10.15179/ces.21.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Bucking the Trend: Female Labor Market Participation in Kosovo

Abstract: This paper adds to the limited research conducted on labor markets with low female labor force participation, providing the first multivariate analysis for Kosovo. The determinants of female labor force participation (FLFP) in Kosovo are investigated utilizing an eclectic model, comprising of individual, household, and socio-economic determinants, to analyze data from the Kosovo Labor Force Survey. Both supply and demand factors contribute to the explanation of the low FLFP in Kosovo. The results confirm that:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Between 2012 and 2019 the average gender gap in employment was about 31 percentage points. Gashi et al (2019) find that both demand and supply factors account for the low FLFP in Kosovo. Their results confirm that age, marital status, educational attainment, local labour market demand and the composition of the household are significant determinants of FLFP.…”
Section: Are Women Really Paid More Than Men In Kosovo? Unpicking the Evidencementioning
confidence: 78%
“…Between 2012 and 2019 the average gender gap in employment was about 31 percentage points. Gashi et al (2019) find that both demand and supply factors account for the low FLFP in Kosovo. Their results confirm that age, marital status, educational attainment, local labour market demand and the composition of the household are significant determinants of FLFP.…”
Section: Are Women Really Paid More Than Men In Kosovo? Unpicking the Evidencementioning
confidence: 78%
“…In Kosovo, this phenomenon is generally more evident than in other WB6 countries. According to Gashi et al (2019) in recent years there is no evidence provided that the labour market outcomes for women in Kosovo have been improving. Therefore, Gashi et al (2019) in their research explore this puzzle, focusing on the causes and low levels of women's participation in the Kosovo labour market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Gashi et al (2019) in recent years there is no evidence provided that the labour market outcomes for women in Kosovo have been improving. Therefore, Gashi et al (2019) in their research explore this puzzle, focusing on the causes and low levels of women's participation in the Kosovo labour market. Their results confirm the found effects of age, marital status, and education on women labour force participation rate (Gashi et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it has been found that the fertility rate, unemployment rate and GDP per capita are significantly and positively related to women's work participation. Gashi et al (2019) explored the determinants of female labor force participation (FLFP) in Kosovo. The authors had employed multivariate analysis and an eclectic model for the econometric analysis.…”
Section: Literature Reviewmentioning
confidence: 99%